IMPROVING STUDENT LEARNING OUTCOMES ACTIVITIES THROUGH THE IMPLEMENTATION OF GAME BASED LEARNING MODEL USED BY SMART HAFIZ MEDIA AND TRADITIONAL GAMES - Yolanda, Kingkin Wieke; Laksana, Dek Ngurah Laba (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This research was conducted over three learning sessions. The subjects were second-grade students at SDN Cibeureum Mandiri 2, Cimahi City, in the 2025/2026 academic year. There were 34 students in this class. This research was motivated by low student activity during learning and a lack of comprehension of fictional stories, resulting in declining learning outcomes. The main objectives of developing and implementing this learning model were to improve learning comprehension, preserve students' traditional game culture, and improve student learning outcomes using the Game-Based Learning (GBL) model assisted by Smart Hafiz and Traditional Games. Data were obtained from student learning activities and employed the Kemmis & McTaggart research design through CAR. Data analysis was calculated based on instruments and indicators in the form of pretests and posttests with 10 questions. The data analysis technique used was the Completion Indicator. The results of the Formative Assessment study on student activity showed a significant increase in student learning outcomes, from 65% (fairly good) in the first meeting to 80% (very good) in the second meeting. Student activity increased to 95% (mostly active) in the third meeting. Analysis of learning outcomes showed a 70% pretest in the first meeting, an 87% pretest in the second meeting, and a 100% pretest in the third meeting. Overall, this study concluded that the combination of learning models was effective in improving student activity and learning outcomes.